Heart Collector Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2015)
Finding murderers is just a day on the job for police captain Nadia Barka. But when a mutilated corpse is discovered in an old baptistery, she’s faced with some difficult questions: Who left a young woman’s body in a high-security museum in the middle of the night? And where is the victim’s heart?Barka has no leads, until several days later when unassuming computer technician Julien Lombard comes forward, claiming to have had a premonition of the woman’s abduction and murder. The ensuing investigation turns up nothing, however, and Julien is just as skeptical about his intel as the police are. But, after another woman goes missing, Barka decides to take a chance and trust in Julien’s gift. Does Julien hold the key to preventing another gruesome crime? Working together, can they find the murderer before he steals another heart?
Keywords: dept.lib; faculty_collection

A theory of the drone. - Dickens, Jeffrey J. (Library Journal, 2015)
Keywords: dept.lib; ⛔ No DOI found

Give us the ballot: the modern struggle for voting rights in america - Dickens, Jeffrey J. (Library Journal, 2015)
Keywords: dept.lib; ⛔ No DOI found

Political animals: how our stone-age brain gets in the way of smart politics. - Dickens, Jeffrey J. (Library Journal, 2015)
Keywords: dept.lib; ⛔ No DOI found